Why have multiple climate policies for light-duty vehicles? Policy mix rationales, interactions and research gaps. (May 2020) - Bhardwaj, Chandan; Axsen, Jonn; Kern, Florian; McCollum, David
Highlights: Reviews literature across disciplines to identify rationales for policy mixes. Qualitatively analyses climate transport policy interactions across multiple criteria. Identifies research gaps and future research agenda for policy mix interactions. Abstract: Globally, there are a wide variety of policies in place that could help contribute to deep greenhouse gas (GHG) emissions reductions in the light-duty vehicle sector. Most regions are impacted by a mix of such policies. However, the transportation literature has devoted little attention to policy mixes, especially in the light-duty vehicles sector, so here we review and draw insights from the broader, mostly non-transport literature. We identify several rationales for pursuing mixes of policies: (i) the "three legs" approach to transport decarbonization, namely that different policies should address different GHG reduction areas (low-carbon fuels, vehicle efficiency and reduced travel demand), (ii) the "market failure" perspective that a different policy is needed to correct each market failure, (iii) the "political process" perspective that considers the real-world need for a policy mix to be perceived as political acceptability, and (iv) the "systems" perspective that policy needs to send signals to channel technological innovation and break the lock-in of incumbent practices. Based on this review, we develop a simple framework for examining policy interactions across multiple criteria, namely GHG mitigation, cost-effectiveness, political acceptability, and transformative signal. We demonstrate this framework by setting hypotheses for interactions across six light-duty vehicle policies in the case of British Columbia, Canada – including a carbon tax, electric vehicle purchase incentives, infrastructure deployment, and three regulations. We conclude with a summary of important research gaps and implications for policy design, as well as quantitative modeling.